Diagnóstico molecular de microorganismos periodonpatógenos en pacientes alcohólicos - fumadores con periodontitis crónica pertenecientes a un Centro de Rehabilitación de la ciudad de Loja, en el periodo marzo - julio 2015 - Aguilar Betancourth, Alexandra Johanna (2015)
The main objective of this work is to determine the presence of periodontopathogens microorganisms: Porphyromonas gingivalis (Pg), Treponema denticola (Td), Tannerella forsythia (Tf), Fusobacterium nucleatum (Fn) and Aggregatibacter actinomycetemcomitans (Aa) through the polymerase chain reaction test (PCR) in alcoholic smokers patients diagnosed with chronic periodontitis, who are provided with special care at the therapeutic community of Loja city. In this way, it was found that alcoholic smokers patients diagnosed with chronic periodontitis of the Therapeutic Community depending on the degree of alcohol and tobacco, frequently present Tannerella forsythia (91.13%), followed by Treponema denticola (56.5% ) and in all patients Fusobacterium nucleatum (100%), these ones were found in a 56.52% inside the risk group of alcoholics, and in 39.13% in the light smokers group. The presence of Aa 21.7%, and a smaller quantity of Pg 13% it was noticed too. These percentages indicate us that it is present a purely aggressive periodontitis. To conclude it can be mentioned that the periodontopathogens microorganisms in study appear at the moment that the polymerase chain reaction test (PCR) was made (PCR). Besides it could clearly demonstrate that patients diagnosed with chronic periodontitis and the ones who have bags equal to 6mm may or may not present all periodontopathogens microorganisms under study, as well as, it can be asserted that the presence of only one microorganisms is enough to allow inflammation of the protection and insertion periodontium. Keywords: PCR - Porphyromonas gingivalis - Treponema denticola - Tannerella forsythia - Aggregatibacter actinomycetemcomitans - Fusobacterium nucleatum